1995
DOI: 10.1037/0096-1523.21.5.1139
|View full text |Cite
|
Sign up to set email alerts
|

Hand coordination in bimanual circle drawing.

Abstract: Two right-handed and 2 left-handed participants drew circles in the horizontal plane with both hands simultaneously in either a symmetrical or an asymmetrical mode, at their preferred rate or as fast as possible. During symmetrical movements, the hands showed frequency and phase synchronization at both rates. During fast asymmetrical movements, the hands showed increased phase difference and phase variability, as well as transitions to symmetrical movements, and cases of frequency decoupling. Large distortions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
86
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 37 publications
15
86
1
1
Order By: Relevance
“…Apart from these new Wndings we replicated some well known phenomena from the literature. That is, reaction times and movement times were longer in bimanual trials compared to unimanual trials (e.g., Kelso et al 1979;Jackson et al 2002;Mason and Bryden 2007), and interlimb coupling was higher when moving in symmetry than in asymmetry (e.g., Swinnen et al 1991;Carson 1995;Semjen et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from these new Wndings we replicated some well known phenomena from the literature. That is, reaction times and movement times were longer in bimanual trials compared to unimanual trials (e.g., Kelso et al 1979;Jackson et al 2002;Mason and Bryden 2007), and interlimb coupling was higher when moving in symmetry than in asymmetry (e.g., Swinnen et al 1991;Carson 1995;Semjen et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…These interference eVects were especially obvious when nonhomologous muscle pairs were activated (Li et al 2004). Ample studies showed an increased stability of arm movements in the symmetric mode (both hands/arms moving mirror-symmetrically with respect to the longitudinal axis of the body) compared to arm movements in the asymmetric mode (both hands/arms moving alternating with respect to the longitudinal axis of the body) (Byblow et al 1994;Semjen et al 1995;Swinnen et al 1997Swinnen et al , 1998Li et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, phase transitions occur earlier for wrist abduction and adduction movements than for wrist flexion and extension movements (see note 3). At a more cognitive level, movements with compatible spatial codes are easier to perform than those in which such codes are incongruent (Franz, Zelaznik, & McCabe, 1991;Semjen, Summers, & Cattaert, 1995), independent of biomechanics. Such codes may be perceptual in nature (Mechsner, 2004a(Mechsner, , 2004bMechsner et al, 2001; see also Kunde & Weigelt, 2005), and/or they may reflect interactions associated with response selection (Ivry et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As such, we have partial data (13 subjects) for right-handed tapping. However, nondominant left-hand movements have been reported to fluctuate more in the BP mode than those of the dominant right hand (Semjen et al, 1995;Aramaki et al, 2006). Thus, we calculated performance indices using left-hand tapping data for all 18 subjects and used it in the correlation analysis with brain activity.…”
Section: Discussionmentioning
confidence: 99%